PERAN MAHASISWA KKN MANAJEMEN PENDIDIKAN KRISTEN IAKN TARUTUNG DALAM MENDUKUNG ADMINISTRASI DAN PELAYANAN PUBLIK SERTA KEGIATAN KEMASYARAKATAN DIKELURAHAN TOMUAN KOTA PEMATANGSIANTAR - Putra Willy Munthe; Tiarlin Simanungkalit; Nissi Sihombing; Indah Lestari Pakpahan; Lola Angel Situmeang; Ruslan Juliana Pardosi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Administrative services, public services, and community activities are essential components of local government administration at the village level. The increasing public demand for fast, accurate, and effective services requires village governments to continuously improve the quality of their services. In supporting this effort, higher education institutions, through the Community Service Program (Kuliah Kerja Nyata/KKN), play a strategic role in implementing the Tri Dharma of Higher Education, particularly community engagement. This article aims to describe the role of students from the Christian Education Management Study Program of the Indonesian Christian State Institute (IAKN) Tarutung in supporting administrative services, public services, and community activities in Tomuan Village, Pematangsiantar City. The community service program employed a participatory and collaborative approach consisting of observation, coordination, implementation, and evaluation stages. Data were collected through observation, documentation, and direct participation during the program and were analyzed using a qualitative descriptive approach. The results indicate that the students contributed to administrative support by assisting in document management, record organization, and administrative reporting. In addition, they supported public services and actively participated in various community activities, including community clean-up programs, environmental initiatives, assistance with the UP2K PKK program, and other social activities. The students' involvement enhanced the effectiveness of administrative and public services while providing valuable practical experience in applying the knowledge and skills acquired during their academic studies. Therefore, the Community Service Program (KKN) serves as a tangible form of collaboration between higher education institutions and local government in improving the quality of public services and promoting community empowerment.